2022
DOI: 10.3390/ijms23031328
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptosis Paradox in Cancer

Abstract: Cancer growth represents a dysregulated imbalance between cell gain and cell loss, where the rate of proliferating mutant tumour cells exceeds the rate of those that die. Apoptosis, the most renowned form of programmed cell death, operates as a key physiological mechanism that limits cell population expansion, either to maintain tissue homeostasis or to remove potentially harmful cells, such as those that have sustained DNA damage. Paradoxically, high-grade cancers are generally associated with high constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(104 citation statements)
references
References 134 publications
0
68
0
Order By: Relevance
“…prevent growth and metastasis of tumors (71). As a tumor suppressor gene, TP53 plays an important role in regulating apoptosis.…”
Section: Role Of Tp53 Mutation In Apoptosismentioning
confidence: 99%
“…prevent growth and metastasis of tumors (71). As a tumor suppressor gene, TP53 plays an important role in regulating apoptosis.…”
Section: Role Of Tp53 Mutation In Apoptosismentioning
confidence: 99%
“…The enrichment scores of cell pathways, such as tumour proliferation, epithelialmesenchymal transition (EMT), angiogenesis, and apoptosis, were higher in the high-risk group, also suggesting that the AAM-related gene signature plays an essential role in the tumourigenesis and progression in ccRCC. Some studies demonstrated that tumours with higher levels of apoptosis are more aggressive (Morana et al, 2022). Thus, the above-selected gene, consisting of an AAM-related gene signature, plays an essential role in cancer progression and prognosis prediction for ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…The process of apoptosis can be roughly divided into the following stages: receiving apoptosis signal → interaction between apoptosis regulating molecules → activation of proteolytic enzyme (Caspase) → entering a continuous reaction process ( 13 ). Due to the different initiation stages of apoptosis, the signaling pathway of apoptosis can be divided into three main pathways, namely mitochondrial pathway, endoplasmic reticulum pathway, and death receptor pathway.…”
Section: Discussionmentioning
confidence: 99%